Intrinsic stretchable cross-linked polymer, preparation method and application thereof, and reverse organic solar cell
Through crosslinked polymers with quinone-type small molecules and amine-containing polymers, the stretchability and air stability of electron transport materials in reverse organic solar cell devices are solved, and high-efficiency solar cell performance is achieved.
Patent Information
- Application Number
- CN202411251746.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The prior art is difficult to develop materials with intrinsic stretchability and high electron transport rates, which limits the air stability and performance of reverse organic solar cell devices.
Crosslinked polymers combined with quinone small molecules and amine-containing polymers are prepared by C-C bond coupling reaction and air oxidation to form crosslinked polymers with good mechanical properties and high electron transport rate.
The intrinsic tensileability and high conductivity of crosslinked polymers are achieved, the energy conversion efficiency and air stability of reverse organic solar cells are improved, and the high efficiency can be maintained under 20% strain conditions.
Smart Images

Figure CN119751861A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic functional materials, and in particular to an intrinsically stretchable cross-linked polymer, a preparation method and application thereof, and a reverse organic solar cell. Background Art
[0002] In recent years, wearable electronic devices have made great progress in the fields of wearable electronic displays, energy devices, biomedicine and robotics. In order to meet these needs, the research and development of intrinsically flexible and stretchable organic electronic devices is crucial. Among them, portable wearable power supplies as power supply devices are an important problem restricting the development of this field.
[0003] Organic solar cells have the advantages of being lightweight, flexible, and capable of large-area roll-to-roll printing. In particular, the superior mechanical properties of organic materials make organic solar cells a strong candidate power source for wearable electronic devices. The energy conversion efficiency of organic solar cells based on hard substrates has exceeded 19%, which has basically met the needs of commercial use. However, fully stretchable organic solar cell devices are in their infancy. Current research on fully stretchable organic solar cells is based on traditional configuration devices. Since the top electrode is the cathode, there is a defect of poor air stability. A large number of studies have confirmed that reverse configuration devices with the top electrode as the anode can significantly improve the air stability of the device, making organic solar cells more valuable. However, due to the problem that intrinsically stretchable electron transport materials will be dissolved by conventional solvents and have low conductivity, intrinsically stretchable devices based on reverse configurations have never been reported. Therefore, the development of intrinsically stretchable electron transport materials is a difficult problem that needs to be solved urgently in this field. Summary of the invention
[0004] The object of the present invention is to provide an intrinsically stretchable cross-linked polymer, a preparation method and application thereof, and an inverse organic solar cell. The cross-linked polymer can be used as an electron transport layer in an inverse organic solar cell.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides an intrinsically stretchable cross-linked polymer, the preparation raw materials of which include quinone-type small molecules and amine-containing polymers;
[0007] The quinone-type small molecule has a structure shown in Formula 1 or 2:
[0008] Preferably, the mass ratio of the quinone-type small molecule to the amine-containing polymer is (7-3): (3-7).
[0009] Preferably, the amine-containing polymer includes one or more of polyethyleneimine, polyethoxyethyleneimine and ε-polylysine.
[0010] Preferably, the preparation method of the quinone-type small molecule comprises the following steps:
[0011] Mixing a compound having a structure shown in Formula 3 or a compound having a structure shown in Formula 4, 1,3-indandione, a palladium catalyst, sodium hydride and a solvent, and sequentially performing a CC bond coupling reaction and air oxidation to obtain the quinone-type small molecule;
[0012]
[0013] When the reaction raw material is a compound having a structure shown in Formula 3, the quinone-type small molecule has a structure shown in Formula 1; when the reaction raw material is a compound having a structure shown in Formula 4, the quinone-type small molecule has a structure shown in Formula 2;
[0014] The palladium catalyst is methanesulfonic acid (2-di-tert-butylphosphino-2',4',6'-triisopropyl-1,1'biphenyl) (2'-amino-1,1'-biphenyl-2-yl) palladium (II).
[0015] Preferably, the molar ratio of the compound having the structure shown in Formula 3 or the compound having the structure shown in Formula 4, 1,3-indandione, palladium catalyst and sodium hydride is 1:(2.2-3):(0.01-0.10):(4.2-5).
[0016] Preferably, the temperature of the CC bond coupling reaction is 70-100°C and the time is 1-12h;
[0017] The air oxidation is carried out at a temperature of room temperature to 60° C. and for a time of 10 to 60 minutes.
[0018] The present invention also provides a method for preparing the cross-linked polymer described in the above technical solution, comprising the following steps:
[0019] The quinone-type small molecule, the amine-containing polymer and the organic solvent are mixed, and then spin-coated and thermally annealed in sequence to obtain the cross-linked polymer.
[0020] Preferably, the thermal annealing temperature is room temperature to 200° C., and the time is 10 to 30 minutes.
[0021] The present invention also provides the use of the cross-linked polymer described in the above technical solution or the cross-linked polymer prepared by the preparation method described in the above technical solution as an electron transport material in an inverted organic solar cell device.
[0022] The present invention also provides an inverted organic solar cell, comprising a substrate, a cathode, an electron transport layer, an active layer, a hole transport layer and an anode stacked in sequence from bottom to top, characterized in that the material of the electron transport layer is the cross-linked polymer described in the above technical solution or the cross-linked polymer prepared by the preparation method described in the above technical solution.
[0023] The present invention provides an intrinsically stretchable cross-linked polymer, the preparation raw materials of which include quinone-type small molecules and amine-containing polymers;
[0024] The quinone-type small molecule has a structure shown in Formula 1 or 2:
[0025] The introduction of the quinone-type small molecules of the present invention can improve the electron transport properties of the cross-linked polymer, making its conductivity reach 0.049S·m -1 At the same time, since the amine groups on the amine-containing polymer will react with the receptor materials (e.g., L8-BO, BTP-eC9, etc.) in the subsequent solar cells after being applied to the solar cells, the chemical structure of the quinone-type small molecules of the structure shown in Formula 1 described in the present application react with the amine groups in the polyethyleneimine to convert the amine groups into quaternary ammonium salts (ionize the amine groups), which can passivate the chemical reaction activity of PEI with non-fullerene receptors. The cross-linked polymer network can effectively dissipate stress, so that the cross-linked polymer has good mechanical properties, and the crack initiation strain (COS) reaches 46%;
[0026] The present invention also provides the use of the cross-linked polymer described in the above technical solution or the cross-linked polymer prepared by the preparation method described in the above technical solution as an electron transport material in a reverse organic solar cell device. Since the cross-linked polymer contains abundant strong polar amine groups, it can modify the metallized electrode to form an ohmic contact between the active layer and the metal electrode, promote the extraction and transmission of electrons, and help improve the energy conversion efficiency of organic solar cells. The energy conversion efficiency of the reverse organic solar cell device prepared based on it reaches 18.27%. The energy conversion efficiency of the fully stretchable reverse organic solar cell prepared based on it reaches 14.01%. Under the condition of 20% strain, it can still maintain about 70% of the initial efficiency after 500 cycles of stretching. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the H-NMR spectrum of the quinone-type small molecule having the structure shown in Formula 1 described in Example 1 of the present invention;
[0028] Figure 2 This is the NMR carbon spectrum of the quinone-type small molecule having the structure shown in Formula 1 described in Example 1 of the present invention;
[0029] Figure 3 This is a high-resolution mass spectrum of the quinone-type small molecule having the structure shown in Formula 1 described in Example 1 of the present invention;
[0030] Figure 4 Schematic diagram of the structure of the inverted organic solar cell device described in Application Example 2, wherein 1 is a TPU layer, 2 is a PH1000 layer, 3 is a QBr-PEI-50 layer, 4 is an active material layer, 5 is a PEDOT:F layer, and 6 is an EGaln layer;
[0031] Figure 5 The JV curve of the inverted organic solar cell device described in Application Example 1;
[0032] Figure 6 This is the JV curve of the inverted organic solar cell device described in Application Example 2. DETAILED DESCRIPTION
[0033] The present invention provides an intrinsically stretchable cross-linked polymer, the preparation raw materials of which include quinone-type small molecules and amine-containing polymers;
[0034] The quinone-type small molecule has a structure shown in Formula 1 or 2:
[0035]
[0036] In the present invention, the mass ratio of the quinone-type small molecule to the amine-containing polymer is preferably (7-3): (3-7), more preferably (6-4): (4-6), and most preferably (5.5-4.5): (4.5-5.5). In an embodiment of the present invention, the mass ratio of the quinone-type small molecule to the amine-containing polymer may be 1:1.
[0037] In the present invention, the amine-containing polymer preferably includes one or more of polyethyleneimine (PEI), polyethoxyethyleneimine (PEIE) and ε-polylysine (ε-PL).
[0038] In the present invention, the preparation method of the quinone-type small molecule comprises the following steps:
[0039] Mixing a compound having a structure shown in Formula 3 or a compound having a structure shown in Formula 4, 1,3-indandione, a palladium catalyst, sodium hydride and a solvent, and sequentially performing a CC bond coupling reaction and air oxidation to obtain the quinone-type small molecule;
[0040]
[0041] When the reaction raw material is a compound having a structure shown in Formula 3, the quinone-type small molecule has a structure shown in Formula 1; when the reaction raw material is a compound having a structure shown in Formula 4, the quinone-type small molecule has a structure shown in Formula 2;
[0042] The palladium catalyst is methanesulfonic acid (2-di-tert-butylphosphino-2',4',6'-triisopropyl-1,1'biphenyl) (2'-amino-1,1'-biphenyl-2-yl) palladium (II).
[0043] In the present invention, the solvent is preferably one or more of 1,6-dioxane, tetrahydrofuran and toluene. In an embodiment of the present invention, the solvent may be 1,6-dioxane.
[0044] In the present invention, the molar ratio of the compound having the structure shown in Formula 3 or the compound having the structure shown in Formula 4, 1,3-indanedione, the palladium catalyst and sodium hydride is preferably 1: (2.2-3): (0.01-0.10): (4.2-5). In an embodiment of the present invention, the molar ratio of the compound having the structure shown in Formula 3, 1,3-indanedione, the palladium catalyst and sodium hydride can be 1: 2.2: 0.02: 4.6. The present invention does not have any special limitation on the amount of the solvent, and the amount well known to those skilled in the art can be used to ensure the smooth progress of the reaction.
[0045] The present invention does not have any special limitation on the mixing process, and the mixing process may be carried out using a process well known to those skilled in the art.
[0046] In the present invention, the temperature of the C-C bond coupling reaction is preferably 70 to 100°C, more preferably 70°C, and the time is preferably 1 to 12 hours, more preferably 2 hours; the temperature of the air oxidation is preferably room temperature to 60°C, more preferably room temperature, and the time is preferably 10 to 60 minutes, more preferably 30 minutes. In an embodiment of the present invention, the temperature of the C-C bond coupling reaction can be 70°C, the time can be 2 hours, the temperature of the air oxidation can be room temperature, and the time can be 30 minutes.
[0047] The present invention also provides a method for preparing the cross-linked polymer described in the above technical solution, comprising the following steps:
[0048] The quinone-type small molecule, the amine-containing polymer and the organic solvent are mixed, and then spin-coated and thermally annealed in sequence to obtain the cross-linked polymer.
[0049] In the present invention, the organic solvent preferably includes one or more of chloroform, chlorobenzene, toluene, N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO). When the organic solvent is two or more of the above specific selections, the present invention does not have any special restrictions on the ratio of the above specific substances, and can be mixed in any ratio. The present invention does not have any special restrictions on the amount of the organic solvent, and the amount familiar to those skilled in the art can be used to ensure that the reaction proceeds smoothly. In an embodiment of the present invention, the amount ratio of PEI and organic solvent can be 2.5mg:1mL.
[0050] The present invention does not have any special limitation on the mixing process, and the mixing process may be carried out using a process well known to those skilled in the art.
[0051] In the present invention, the spin coating speed is preferably 1000-3000 rpm, and the time is preferably 30-90 s. In an embodiment of the present invention, the spin coating speed may be 2000 rpm, and the time may be 60 s.
[0052] In the present invention, the thermal annealing temperature is preferably room temperature to 200°C, more preferably 100 to 150°C, and the time is preferably 10 to 30 minutes, more preferably 20 minutes. In an embodiment of the present invention, the thermal annealing temperature can be 120°C, and the time can be 20 minutes.
[0053] The present invention also provides the use of the cross-linked polymer described in the above technical solution or the cross-linked polymer prepared by the preparation method described in the above technical solution as an electron transport material in an inverted organic solar cell device.
[0054] In the present invention, the inverted organic solar cell device is preferably a hard substrate cell or a fully stretchable cell.
[0055] In the present invention, the inverted organic solar cell device comprises a substrate, a cathode, an electron transport layer, an active layer, a hole transport layer and an anode stacked in sequence from bottom to top. The material of the electron transport layer is the cross-linked polymer described in the above technical solution or the cross-linked polymer prepared by the preparation method described in the above technical solution.
[0056] When the inverted organic solar cell device is a hard substrate battery, the material of the substrate in the inverted organic solar cell device is preferably a glass substrate, and the material of the cathode is preferably ITO; the material of the electron transport layer is preferably the cross-linked polymer described in the above technical solution or the cross-linked polymer prepared by the preparation method described in the above technical solution; the material of the active layer is preferably a donor and an acceptor with a mass ratio of 1:1.3, the donor is preferably PM6 (the structural formula is shown in Formula 5), and the acceptor is preferably L8-B0 (the structural formula is shown in Formula 6) and BTP-eC9 (the structural formula is shown in Formula 7) with a mass ratio of 0.9:0.4; the material of the hole transport layer is preferably molybdenum oxide; and the material of the anode is preferably silver.
[0057] When the inverted organic solar cell device is a fully stretchable cell, the material of the substrate in the inverted organic solar cell device is preferably thermoplastic polyurethane elastomer (TPU), the material of the cathode is preferably poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid (PH1000); the material of the electron transport layer is preferably the cross-linked polymer described in the above technical solution or the cross-linked polymer prepared by the preparation method described in the above technical solution; the material of the active layer is preferably PM6 and FDA-m-TAT (structural formula shown in Formula 8) with a mass ratio of 1:1.2; the material of the hole transport layer is preferably PEDOT:F; the material of the anode is preferably gallium-indium alloy (EGaIn);
[0058]
[0059] The intrinsically stretchable cross-linked polymer provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0060] Example 1
[0061] According to a molar ratio of 1:2.2:0.02:4.6, a compound having a structure represented by Formula 2, 1,3-indandione, methanesulfonic acid (2-di-tert-butylphosphino-2',4',6'-triisopropyl-1,1'biphenyl) (2'-amino-1,1'-biphenyl-2-yl) palladium (II) and sodium hydride are mixed, and then mixed with an organic solvent (1,6-dioxane) to obtain a reaction solution having a concentration of 0.1 mol / L of the compound having a structure represented by Formula 2;
[0062] The obtained reaction solution was heated and stirred at 70° C. for 2 h, and then oxidized in air for 30 min (temperature was room temperature) to obtain a quinone-type small molecule having a structure shown in Formula 1;
[0063] In a glove box filled with argon, 2.5 mg of the quinone-type small molecule having the structure shown in Formula 1, 2.5 mg of PEI and 1 mL of DMF were added to a sample bottle, the obtained spin coating solution was spin coated at a speed of 2000 rpm for 60 seconds, and the prepared film was thermally annealed on a hot plate at 120° C. for 20 minutes to obtain a cross-linked polymer film (denoted as QBr-PEI-50);
[0064] Figure 1 is the nuclear magnetic hydrogen spectrum of the quinone-type small molecule having the structure shown in Formula 1, Figure 1 It can be seen that the number of hydrogen atoms is consistent with the molecule described in Formula 1, and the number of hydrogen atoms at the chemical shifts of 8.02, 7.92 and 7.72 ppm is consistent with the molecular structure, which can confirm that the structure described in Formula 1 is correct;
[0065] Figure 2 is the NMR carbon spectrum of the quinone-type small molecule having the structure shown in Formula 1, Figure 2 It can be seen that the number of carbon atoms is consistent with the molecule described in Formula 1, and it can be determined that the structure described in Formula 1 is correct;
[0066] Figure 3 is a high-resolution mass spectrum of the quinone-type small molecule having the structure shown in Formula 1, Figure 3 It can be seen that the mass-to-nuclear ratio obtained from the test is consistent with the theoretical value, which confirms that the structure described in Formula 1 is correct.
[0067] Example 2
[0068] Refer to Example 1, except that the total concentration of the quinone-type small molecule having the structure shown in Formula 1 and PEI in the spin coating solution is 10 mg / mL.
[0069] Test Case
[0070] The conductivity of QBr-PEI-50 described in Example 2 was tested by a four-probe method: the spin coating solution described in Example 2 was spin-coated onto Corning glass with a gold electrode at 3000 rpm, annealed on a hot plate at 120° C. for 20 min, and tested using Keysight B2902A. The test result was: the conductivity was 0.049 S·m -1 ;
[0071] Poly(4-styrenesulfonic acid) (PSS) and water were mixed in a volume ratio of 1:4, and then spin-coated on glass at a speed of 3000 rpm for 40 s, and then placed in an oven at 160 °C for 20 min to obtain a PSS layer;
[0072] The spin coating liquid of Example 2 was spin coated onto the surface of the PSS layer at 3000 rpm, and after annealing on a hot stage at 120° C. for 20 min, the obtained cross-linked polymer film was adhered to a polydimethylsiloxane (PDMS) substrate, and after being soaked in water to dissolve the PSS, the film was transferred to the PDMS substrate and a crack initiation strain (COS) test was performed. The test method was: measuring the initial length l0 of the film after transfer, performing an in-situ tensile test under a polarizing microscope, and measuring the film length l when a crack appeared, then COS=(l-l0) / l0. The test result showed that COS was 46%.
[0073] Application Example 1
[0074] Fabrication of inverted organic solar cells on ITO substrates:
[0075] The ITO glass was ultrasonically cleaned with soapy water, deionized water, acetone and isopropanol for 20 min in sequence, and then treated with an ultraviolet ozone cleaner (UVO) for 25 min to obtain a pretreated ITO substrate (thickness of 100 nm);
[0076] In a glove box filled with argon, the spin coating solution with a concentration of 5 mg / mL described in Example 1 was spin coated at 2000 rpm for 60 seconds, and then annealed on a hot stage at 120° C. for 20 minutes to obtain an electron transport layer (with a thickness of 30 nm);
[0077] PM6, L8-BO and BTP-eC9 were mixed in a mass ratio of 1:0.9:0.4, and a 17 mg / mL solution was prepared with chloroform. The obtained solution was spin-coated on the surface of the electron transport layer (rotation speed of 3000 rpm, time of 30 s), and then annealed at 100 ° C for 10 min to obtain an active layer (thickness of 100 nm);
[0078] Vacuum evaporation equipment was used to evaporate 2 nm thick molybdenum oxide to obtain a hole transport layer (hole transport layer) (thickness 2 nm);
[0079] 150 nm of silver was evaporated on the surface of the hole transport layer to obtain an anode layer (thickness of 150 nm), and finally a hard substrate battery (inverted organic solar cell device) was obtained, and the performance parameters are shown in Table 1;
[0080] Table 1 Performance parameters of the inverted organic solar cell device
[0081] <![CDATA[V OC (V)]]> <![CDATA[J SC (mA / cm 2 )]]> FF(%) PCE(%) 0.859 77.56 27.43 18.27
[0082] Note: V OC is the open circuit voltage, J SC is the short-circuit current, FF is the fill factor, and PCE is the power conversion efficiency.
[0083] Figure 5 is the JV curve of the inverse organic solar cell device, Figure 5 As shown in Table 1, the V oc =0.859V,J sc =77.56mA / cm 2 , FF is 27.43%; an energy conversion efficiency of 18.27% can be obtained using QBr-PEI-50 as the electron transport layer, which is one of the highest values based on the inverse device structure.
[0084] Application Example 2
[0085] Preparation of inverse organic solar cells (fully stretchable inverse organic solar cells):
[0086] After TPU (thickness 2 μm) was treated with oxygen plasma (O-Plasma) for 10 min, PH1000 was spin-coated at 1000 rpm for 30 s and annealed on a hot stage at 110 °C for 20 min to obtain a cathode layer (thickness 100 nm);
[0087] In a glove box filled with argon, the spin coating solution with a concentration of 5 mg / mL described in Example 1 was spin coated at 2000 rpm for 60 seconds, and then annealed on a hot stage at 120° C. for 20 minutes to obtain an electron transport layer (with a thickness of 30 nm);
[0088] PM6 and FDA-m-TAT were mixed at a mass ratio of 1:1.2, and then prepared into a 17 mg / mL solution with chloroform. The obtained solution was spin-coated on the surface of the electron transport layer (3000 rpm, 30 s), and then annealed at 100°C for 10 min to obtain an active layer (100 nm thick);
[0089] After spin coating PEDOT:F on the surface of the active layer (4000 rpm, 30 s), annealing at 100° C. for 5 min to obtain a hole transport layer (30 nm thick);
[0090] Finally, liquid metal EGaIn is sprayed on the surface of the hole transport layer to obtain an anode layer (thickness of 1000 nm), and finally a fully stretchable battery (inverse organic solar cell device, the structural schematic diagram is shown in FIG. Figure 4 The performance parameters are shown in Table 2.
[0091] Table 2 Performance parameters of the inverted organic solar cell device
[0092] <![CDATA[V OC (V)]]> <![CDATA[J SC (mA / cm 2 )]]> FF(%) PCE(%) <![CDATA[PCE 80% (%)]]> 0.901 66.24 23.50 14.01 21
[0093] Note: V OC is the open circuit voltage, JSC is the short-circuit current, FF is the fill factor, PCE is the energy conversion efficiency, PCE 80% The strain when the device efficiency decays to 80% of the initial efficiency;
[0094] Figure 6 is the JV curve of the inverse organic solar cell device, Figure 6 It can be seen that the Voc of the fully stretchable inverse organic solar cell is 0.901V, Jsc is 66.24mA / cm 2 , FF is 23.50%. From Table 2 and Figure 6 It can be seen that the fully stretchable battery successfully prepared by the cross-linked polymer of the present invention can achieve an energy conversion efficiency of up to 14.01%. The device was stretched and tested, and the PCE 80% It reaches 21%. Under the condition of 20% strain, it can still maintain about 70% of the initial efficiency after 500 cycles of stretching, indicating that the device has good mechanical properties.
[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An intrinsically stretchable cross-linked polymer, characterized in that: The preparation raw materials include quinone-type small molecules and amine-containing polymers; The quinone-type small molecule has a structure shown in Formula 1 or 2:
2. The cross-linked polymer according to claim 1, characterized in that The mass ratio of the quinone-type small molecule to the amine-containing polymer is (7-3): (3-7).
3. The cross-linked polymer according to claim 1 or 2, characterized in that The amine-containing polymer includes one or more of polyethyleneimine, polyethoxyethyleneimine and ε-polylysine.
4. The cross-linked polymer according to claim 1 or 2, characterized in that The preparation method of the quinone-type small molecule comprises the following steps: Mixing a compound having a structure shown in Formula 3 or a compound having a structure shown in Formula 4, 1,3-indandione, a palladium catalyst, sodium hydride and a solvent, and sequentially performing a CC bond coupling reaction and air oxidation to obtain the quinone-type small molecule; When the reaction raw material is a compound having a structure shown in Formula 3, the quinone-type small molecule has a structure shown in Formula 1; when the reaction raw material is a compound having a structure shown in Formula 4, the quinone-type small molecule has a structure shown in Formula 2; The palladium catalyst is methanesulfonic acid (2-di-tert-butylphosphino-2',4',6'-triisopropyl-1,1'biphenyl) (2'-amino-1,1'-biphenyl-2-yl) palladium (II).
5. The cross-linked polymer according to claim 4, characterized in that The molar ratio of the compound having the structure shown in Formula 3 or the compound having the structure shown in Formula 4, 1,3-indandione, palladium catalyst and sodium hydride is 1:(2.2-3):(0.01-0.10):(4.2-5).
6. The cross-linked polymer according to claim 5, characterized in that The temperature of the CC bond coupling reaction is 70-100°C and the time is 1-12h; The air oxidation is carried out at a temperature of room temperature to 60° C. and for a time of 10 to 60 minutes.
7. The method for preparing a cross-linked polymer according to any one of claims 1 to 6, characterized in that: The following steps are involved: The cross-linked polymer is obtained by mixing quinone-type small molecules, an amine-containing polymer and an organic solvent, and then performing spin coating and thermal annealing in sequence.
8. The preparation method according to claim 7, characterized in that: The thermal annealing temperature is room temperature to 200° C., and the time is 10 to 30 minutes.
9. Use of the cross-linked polymer according to any one of claims 1 to 6 or the cross-linked polymer prepared by the preparation method according to any one of claims 7 or 8 as an electron transport material in an inverted organic solar cell device.
10. An inverted organic solar cell, comprising a substrate, a cathode, an electron transport layer, an active layer, a hole transport layer and an anode stacked in sequence from bottom to top, characterized in that: The material of the electron transport layer is the cross-linked polymer described in any one of claims 1 to 6 or the cross-linked polymer prepared by the preparation method described in any one of claims 7 or 8.
Citation Information
Patent Citations
Flexible stretchable organic polymer solar cell and preparation method thereof
CN114639781A
Efficient intrinsic stretchable organic solar cell and preparation method thereof
CN116887647A
Preparation method of intrinsic stretchable organic solar cell
CN116916665A
Intrinsically stretchable organic solar cell, manufacturing method thereof and electronic device comprising the same
US20230094693A1
KR20240073481A